GOOD CORPORATE GOVERNANCE, FINANCIAL PERFORMANCE, AND FIRM VALUE: EVIDENCE IN INDONESIA - Wikan Isthika; Melati Oktafiyani; Fadia Zulfa Kanaya (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2025)
This study aims to see the influence of good corporate governance and financial performance on the value of companies in Indonesia. Good Corporate governance uses variable institutional ownership and subsequent managerial ownership for financial performance using profitability. This study uses a population, namely all property and real estate sector companies listed on the Indonesia Stock Exchange, with a research period of 3 years, namely 2019 – 2021. The sample selection method used is the purposive sampling method, which uses the criteria of companies that earn profits and have complete data for three consecutive years. The model used in this study is multiple linear regression using Eviews software version 10. The results showed that the institutional ownership and profitability variables did not affect the value of companies in the property and real estate sectors in the study period. Meanwhile, managerial ownership variables are proven to affect the value of property and real estate companies. The more significant the proportion of managerial ownership in a company, the more management will tend to be more active in maximizing the Company's value.